Dye sensitized solar cell (DSSC) - Zou, Xin (2013)
DSSC is a low-cost, high-efficiency solar cell based on dye-sensitized nano-crystalline film of TiO2. It is differentiated from the conventional solar cells due to its simple fabrication. [1st Award]